# In each of the fo

We have,

f(x) = 4x3-12x2+14x-3 and g(x) = 2x-1

Therefore, by remainder theorem when f (x) is divided by g (x) = 2 (x - ), the remainder is equal to f ()

Now, f(x) = 4x3-12x2+14x-3

f () = 4 ()3 – 12 ()2 + 14 () – 3

= (4 * ) – (12 * ) + 7 – 3

= – 3 + 7 – 3

=

Hence, required remainder is

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Master the Art of Writing Chemical Formulae42 mins
Combinations of Solids43 mins
Law of Gravitation40 mins
Newton's Second Law46 mins
Master Mole Concept in 45 Minutes48 mins
Quick Recap of Cell62 mins
Circles- All kinds of Questions36 mins
Arc of Circle And Related IMP Qs40 mins
Surface Area and Volume of solids Revision43 mins
Newton's Third Law44 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x31</sRS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x3RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics